Expediente (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
We present here the Editorial Board an d Board of Reviewers that make up Urdimento - Journal of Studies in Performing Arts, v.4, n. 49, 2023
Keywords: Expediente; Board of reviewers; Editorial board